Atopy patch test with Aleuroglyphus ovatus antigen in patients with atopic dermatitis. (13th March 2014) - Lorenzini, D.; Pires, M.; Aoki, V.; Takaoka, R.; Souza, R.L.; Vasconcellos, C.
Abstract Background Epicutaneous test made with dust mite antigens. Objective Evaluation of the response of the epicutaneous test with Aleuroglyphus ovatus antigen in atopic patients. Methods We patch tested 119 individuals, 48 with atopic dermatitis, 50 with respiratory allergy and 21 healthy controls. We compare the positive response frequency to a closed patch test using Aleuroglyphus ovatus antigen in different concentrations and 48 and 96h reading times among those individuals. Results Six patients with atopic dermatitis (12.5%) and 4 with respiratory atopy (8.0%) had positive reactions. None of the non‐atopic controls had a positive response. As the antigen concentration raised, the number of positive reactions to epicutaneous test raised as well. Conclusion Our data suggest a positive relation between Atopy Patch Test positive responses and Aleuroglyphus ovatus antigen concentration, no matter the kind of the atopic clinical expression.